Answer:
80
Explanation:
46 + 37 = 83 so 83 rounded to the nearest 10 is 80
Answer:
80
Step-by-step explanation:
46+37 = 83
Rounding to the nearest ten
80
Which inequality matches the graph?
[tex] - 2x + 3y > 7[/tex]
[tex]2x - 3y < 7[/tex]
[tex] - 3x + 2y \geqslant 7[/tex]
[tex]3x - 2y \leqslant 7[/tex]
Answer:
[tex]\large\boxed{-3x+2y\geq7}[/tex]
Step-by-step explanation:
<, > - dotted line
≤, ≥ - solid line
<, ≤ - shaded region below the line
>, ≥ - shaded region above the line
====================================
We have solid line (≤, ≥).
Shaded region is above the line (>, ≥)
Therefore, the inequality sign must be: ≥
Finally, your answer is -3x + 2y ≥ 7.
Check the equation of a line.
The point-slope form of an equation of a line:
[tex]y-y_1=m(x-x_1)[/tex]
[tex]m=\dfrac{y_2-y_1}{x_2-x_1}[/tex]
From the graph we ahve the points (3, 8) and (1, 5) - look at the picture.
Substitute:
[tex]m=\dfrac{5-8}{1-3}=\dfrac{-3}{-2}=\dfrac{3}{2}[/tex]
[tex]y-8=\dfrac{3}{2}(x-3)[/tex]
Convert to the standard form [tex]Ax+By=C[/tex]:
[tex]y-8=\dfrac{3}{2}(x-3)[/tex] multiply both sides by 2
[tex]2y-16=3(x-3)[/tex] use the distributive property
[tex]2y-16=3x-9[/tex] subtract 3x from both sides
[tex]-3x+2y-16=-9[/tex] add 16 to both sides
[tex]-3x+2y=7[/tex] CORRECT :)
The amount of energy a microwave oven uses (in the form of electricity) is given by the function f(x)=5x+9, where x is the amount of time the microwave is turned on. The amount of energy the microwave puts out is modeled by the function g(x)=−x^2+3x+1, where x is the amount of time the microwave is turned on.
What is the difference between the amount of energy the microwave uses and the amount it puts out?
(x)=x^2+2x+8
f(x)=−x^2−2x−8
f(x)=−x^2+8x+10
f(x)=x^2−8x−10
Answer:
The difference between the amount of energy the microwave uses and the amount it puts out is x² + 2x + 8 ⇒ first answer
Step-by-step explanation:
* Lets explain how to solve the problem
- The amount of energy a microwave oven uses is given by the
function f(x) = 5x + 9
- The amount of energy the microwave puts out is given by the
function g(x) = − x² + 3x + 1
- x is the amount of time the microwave is turned on in
both functions
- To find the difference between the amount of energy the
microwave uses and the amount it puts out we will subtract
g(x) from f(x)
* Lets do that
∵ f(x) = 5x + 9
∵ g(x) = - x² + 3x + 1
∴ The difference = 5x + 9 - (-x² + 3x + 1) ⇒ multiply the bracket by (-)
- Remember that (-)(-) = (+) and (-)(+) = (-)
∴ The difference = 5x + 9 + x² - 3x - 1 ⇒ Add the like terms
∴ The difference = x² + (5x - 3x) + (9 - 1)
∴ The difference = x² + 2x + 8
* The difference between the amount of energy the microwave uses
and the amount it puts out is x² + 2x + 8
To find the difference between the energy a microwave uses and the energy it puts out, subtract the output function from the input function using the given equations. The correct answer is [tex]f(x) - g(x) = x^2 + 2x + 8[/tex] that is option A is correct.
The difference between the amount of energy the microwave uses and the amount it puts out can be calculated by subtracting the output function from the input function.
Given:
f(x) = 5x + 9 (energy used by the microwave)
[tex]g(x) = -x^2 + 3x + 1[/tex](energy output by the microwave)
Calculating the difference:
Substitute the values:
[tex]f(x) - g(x) = (5x + 9) - (-x^2 + 3x + 1)[/tex]
Simplify the expression:
[tex]f(x) - g(x) = x^2 + 2x + 8[/tex]
I need help breaking this down
Answer:
see explanation
Step-by-step explanation:
Given
2cosΘ - [tex]\sqrt{2}[/tex] = 0 ( add [tex]\sqrt{2}[/tex] to both sides )
2cosΘ = [tex]\sqrt{2}[/tex] ( divide both sides by 2 )
cosΘ = [tex]\frac{\sqrt{2} }{2}[/tex]
Since cosΘ > 0 then Θ is in first and fourth quadrants, hence
Θ = [tex]cos^{-1}[/tex] ( [tex]\frac{\sqrt{2} }{2}[/tex] ) = [tex]\frac{\pi }{4}[/tex]
OR
Θ = 2π - [tex]\frac{\pi }{4}[/tex] = [tex]\frac{7\pi }{4}[/tex]
solutions are Θ = [tex]\frac{\pi }{4}[/tex], [tex]\frac{7\pi }{4}[/tex]
Answer:
π/4, 7π/4.
Step-by-step explanation:
2 cos O - √2 = 0
2 cos O = √2
cos O = √2/2
This is an angle in 45-45-90 triangle where the sides are in the ratio
1:1:√2 where the cosine of 45 degrees = 1 /√2 = √2/2.
In radians it is π/4.
The cosine is also positive in the fourth quadrant so the other solution is
7π/4.
Emma is 7.8 years old she is 1.2 times older than Gavin how old is Gavin
is c^5 - 49 a difference of squares?
a. yes
b. no
No. Since we cannot factor,
[tex]c^5-49[/tex].
Hope this helps.
r3t40
The correct answer is: b. no [tex]c^5 - 49[/tex] is not a difference of squares
Difference of squares refers to an expression of the form [tex]a^2 - b^2[/tex], which can be factored into [tex](a - b)(a + b)[/tex].
In this case, [tex]c^5 - 49[/tex] cannot be expressed in the form of [tex]a^2 - b^2[/tex] because [tex]c^5[/tex] is not a perfect square (a number raised to the power of 2) since it is c raised to the power of 5. To be a difference of squares, both terms must be perfect squares.
49 on the other is a perfect square of 7 but because of [tex]c^5[/tex] the expression [tex]c^5 - 49[/tex] cannot be converted to the form of [tex]a^2 - b^2[/tex] and is thus not considered a difference of squares.
Thus, The correct answer is: b. no [tex]c^5 - 49[/tex] is not a difference of squares
factor completely
1. 7x^3y+14x^2y^3-7x^2y^2
a - 7x^2(xy+2y^3-y^2)
b - 7x^2y(x+2y^2-y)
c - 7(x^3y+2x^2y^3-x^2y^2
d - prime
2. 5x(x+3)+6(x+3)
a - (x+3)(30x)
b - (x+3)(5x+6)
c - (x+3)(11x)
d - prime
3. 8x^5+2x^4+4x^2
a - prime
b- 2(4x^5+x^4+2x^2)
c - 2x(4x^4+x^3+2x)
d - 2x^2(4x^3+x^2+2)
Answer:
B)
B)
D)
Step-by-step explanation:
1. [tex]7x^3y+14x^2y^3-7x^2y^2[/tex]
The GCF of all the term of the above polynomial is [tex]7x^2y[/tex] , hence we take it outside and form a bracket
[tex]7x^2y(x+2y^2-y)[/tex]
The polynomial within the bracket can not be factorized further hence this is our final answer. Option (B) is the right answer
2. [tex]5x(x+3)+6(x+3)[/tex]
The GCF of all the term of the above polynomial is [tex](x+3)[/tex] , hence we take it outside and form a bracket
[tex](x+3)(5x+6)[/tex]
The polynomial within the bracket can not be factorized further hence this is our final answer. Option (B) is the right answer
3. [tex]8x^5+2x^4+4x^2[/tex]
The GCF of all the term of the above polynomial is [tex]2x^2[/tex] , hence we take it outside and form a bracket
[tex]2x^2(4x^3+x^2+2)[/tex]
The polynomial within the bracket can not be factorized further hence this is our final answer. Option (D) is the right answer
Which linear function represents the line given by the point-slope equation y + 7 = –2/3(x + 6)? Here are the options f(x) = –2/3x – 11, f(x) = –2/3x – 1, f(x) = –2/3 + 3, f(x) = –2/3x + 13.
Answer:
The correct answer is: f(x) = –2/3x – 11
Step-by-step explanation:
We have to convert the line given in point slope form to a form which can be compared by the given options
So,
y+7=-2/3(x+6)
[tex]y=-\frac{2}{3}(x+6)\\ y+7=-\frac{2}{3}x+(6)(-\frac{2}{3}) \\ y+7=-\frac{2}{3}x-4\\y=-\frac{2}{3}x-4-7\\y=-\frac{2}{3}x-11[/tex]
Therefore the correct answer is: f(x) = –2/3x –11 ..
I need help please.
Answer:
Step-by-step explanation:
(x²-6x-3)(7x²-4x+7)= ?
Multiply each term of 2nd bracket with the 1st bracket:
=7x²(x²-6x-3) -4x(x²-6x-3) +7(x²-6x-3)
=7x^4-42x^3-21x^2-4x^3+24x^2+12x+7x^2-42x-21
Now solve the like terms:
=7x^4-46x^3+10x^2-30x-21
Therefore the answer is (x²-6x-3)(7x²-4x+7)=7x^4-46x^3+10x^2-30x-21 ....
The function below describes the relationship between the height H and the width w of a rectangle with area 70 sq. units. H(w)= 70/w What is the domain of the function?
Answer:
[tex]w \ne0[/tex]
Step-by-step explanation:
The area of a rectangle is given by:
[tex]Area = L \times \: W[/tex]
In this case, we have the height replacing the length.
[tex]Area=H\times w[/tex]
The area of the rectangle is 70.
[tex]H\times w = 70[/tex]
Dividing through by w gives:
[tex]H = \frac{70}{w} [/tex]
Or to show that H is dependent on w, we write
[tex]H (w)= \frac{70}{w} [/tex]
[tex]w \ne \: 0[/tex]
Domain is the set of all real numbers for which the function is defined.
Therefore the domain is all real numbers except 0.
Answer:
w>0
Step-by-step explanation:
Multiply. Write the product as one power. A^8 • A^5
Answer:
a^ (13)
Step-by-step explanation:
We know x^b* x^c = x^ (b+c)
a^8 * a^5 = a^ (8+5) = a^ (13)
Answer:
Step-by-step explanation:
The answer would be A^13, because when multiplying exponents with the same base, you just have to adfd the exponents.
michelle wants to listen to 5 compact discs. two compact discs are each 5l minutes long and the other three compact discs are each 46 minutes long. how many hours and minutes will it take michelle to listen to all 5 compact discs?
Answer:
[tex]4\ hours[/tex]
Step-by-step explanation:
we know that
1 hour=60 minutes
we know that
To find out how many hours and minutes it will take Michelle to listen to the 5 CDs, add the times for each CD.
so
[tex]2(51)+3(46)=240\ minutes[/tex]
Convert to hours
[tex]240=240/60=4\ hours[/tex]
A truck with 36-in.-diameter wheels is traveling at 55 mi/h.
Find the angular speed of the wheels in rad/min
Answer:
The angular speed is 3,227 rad/min
Step-by-step explanation:
Remember that
1 mile=63,360 inches
step 1
Find the circumference of the wheels
The circumference is equal to
[tex]C=\pi D[/tex]
we have
[tex]D=36\ in[/tex]
substitute
[tex]C=\pi (36)[/tex]
[tex]C=36\pi\ in[/tex]
step 2
we know that
The speed of the wheel is 55 mi/h
Convert to mi/min
55 mi/h=55/60 mi/min
Convert to in/min
(55/60) mi/min=55*63,360/60 in/min= 58,080 in/min
we know that
The circumference of the wheel subtends a central angle of 2π radians
so
using proportion
Find out how much radians are 58,080 inches
[tex]\frac{36\pi }{2\pi }=\frac{58,080}{x} \\\\x=2*58,080/36\\\\x=3,226.67 \ rad[/tex]
therefore
The angular speed is 3,227 rad/min
Final answer:
To calculate the angular speed in radians per minute for a truck with 36-inch diameter wheels traveling at 55 mi/h, convert the diameter to radius in meters, convert the speed to meters per minute, and then use the relationship v = r theta.
Explanation:
To find the angular speed of the wheels in radians per minute, we can use the relationship between linear speed and angular speed, which is given by v = r * theta, where v is the linear speed, r is the radius of the wheel, and theta is the angular speed.
First, convert the diameter to radius: radius = diameter / 2 = 36 in / 2 = 18 in. Then, convert inches to meters as 1 inch is 0.0254 meters. So, radius in meters = 18 in * 0.0254 m/in = 0.4572 m.
Next, convert the speed from miles per hour to meters per minute:
Convert miles to meters: 1 mile = 1609.34 meters,
Speed in meters per minute: 55 mi/h * 1609.34 m/mi * 1h/60min = 1,486.86 m/min.
Now we can find the angular speed: theta = v / r = 1,486.86 m/min / 0.4572 m = 3,252.3 rad/min.
Two-thirds of the children in the fourth - grade class are girls. If there are 18 girls, what is the total number of children in the class?
For this case, the first thing to do is define a variable.
We have then:
x: total number of childrenThen we write the equation that models the problem:
[tex]\frac {2} {3} x = 18[/tex]
From here, we clear the value of x.
We have then:
[tex]x = \frac {3} {2} (18)\\x = 3 * 9\\x = 27[/tex]
Answer:
the total number of children in the class is:
[tex]x = 27[/tex]
To calculate the total number of children in the fourth-grade class, divide the number of girls by 2 to find one-third of the class, then multiply by 3. The total class size is 27 children.
To find the total number of children in the fourth-grade class, we start by understanding that two-thirds of the children are girls. If there are 18 girls, which is two-thirds of the class, we need to calculate the full class size which constitutes three-thirds (or the whole).
Step 1: Represent two-thirds of the class as 2/3.
Step 2: Equate two-thirds of the class to the number of girls: 2/3 of the class = 18 girls.
Step 3: Find one-third of the class by dividing the number of girls by 2: 18 girls \/ 2 = 9 children.
Step 4: Calculate the full class size (which is three-thirds) by multiplying one-third of the class by 3: 9 children x 3 = 27 children.
Therefore, the total number of children in the fourth-grade class is 27.
Use the quadratic formula to determine the exact solutions to the equation x^2-4x-8=0
The answer is 2+2√3 or 2-2√3
Answer:
[tex]x = 2[/tex]±[tex]\sqrt{12}[/tex]
Step-by-step explanation:
Given the following equation ax^2 + bx + c = 0, the quadratic formula states that the solution to that equation is going to be given by:
[tex]x1 = \frac{-b+\sqrt{b^{2}-4ac } }{2a}[/tex]
[tex]x1 = \frac{-b-\sqrt{b^{2}-4ac } }{2a}[/tex]
In this case, a=1, b=-4 and c=-8. Therefore:
[tex]x1 = \frac{4+\sqrt{(-4)^{2}-4(1)(-8)} }{2}[/tex]
[tex]x1 = \frac{4+\sqrt{48}}{2}[/tex]
[tex]x1 = 2+\sqrt{12}[/tex]
[tex]x2 = \frac{4-\sqrt{(-4)^{2}-4(1)(-8)} }{2}[/tex]
[tex]x2 = \frac{4-\sqrt{48}}{2}[/tex]
[tex]x2 = 2-\sqrt{12}[/tex]
Therefore the solutions are:
[tex]x = 2[/tex]±[tex]\sqrt{12}[/tex]
Two statements are missing reasons. What reasons can be used to justify both statements 2 and 3 ?
Answer:
See explanation
Step-by-step explanation:
The given circle has center O.
A, B,C, and D are points on the circumference of the circle.
We want to prove that: [tex]\angle A\cong \angle D[/tex]
We need to join to B and C as shown in the attachment.
Recall that angle subtended by arc BC at the center is twice the angle subtended at the circumference by the same arc.
This implies that:
[tex] \angle O=2\angle A...(1)[/tex]
[tex]\angle O=2\angle D...(2)[/tex]
The LHS of equation (1) and (2) are equal. Therefore the RHS are also equal.
This implies that:
[tex]2\angle A=2\angle D[/tex]
[tex]\therefore \angle A\cong \angle D[/tex]
Answer:
Inscribed angles theorem
Step-by-step explanation:
Just took test on edg2020
Consider the function f(x)=3/4x+12 what is the y-intercept of f-1(x)
Answer:
y = -16
Step-by-step explanation:
f(x)=3/4x+12 (replace f(x) with y)
y =3/4x+12 (rearrange to express x in terms of y)
y - 12=3/4 x
3/4 x = y - 12
3x = 4(y - 12)
x = (4/3)(y - 12)
x = (4/3)y - (4/3)(12)
x = (4/3)y - 16
[tex]f^{-1}[/tex] (y) = (4/3)y - 16
[tex]f^{-1}[/tex] (x) = (4/3)x - 16
comparing to general form
y = mx + b where b is the y-intercept
b = -16
Hence the y-intercept is y = -16
The value of the y-intercept will be given as y = -16
What is an equation?The equation in mathematics is the relationship between the variables and the number and establishes the relationship between the two or more variables.
f (x) = 3/4x + 12 (replace f(x) with y)
y = 3/4x + 12 (rearrange to express x in terms of y)
y - 12 = 3/4 x
3/4 x = y - 12
3x = 4(y - 12)
x = (4/3)(y - 12)
x = (4/3)y - (4/3)(12)
x = (4/3)y - 16
(y) = (4/3)y - 16
(x) = (4/3)x - 16
Compared to the general form
y = mx + b where b is the y-intercept
b = -16
To know more about equations follow
https://brainly.com/question/2972832
#SPJ2
if 2x - 3 + 3x equals -28 what is the value of x
Answer:
x = -5
Step-by-step explanation:
It just is :)
For this case we must find the value of "x" of the following expression:
[tex]2x-3 + 3x = -28[/tex]
We add similar terms:
[tex]5x-3 = -28[/tex]
We add 3 to both sides of the equation:
[tex]5x = -28 + 3[/tex]
Different signs are subtracted and the sign of the major is placed:
[tex]5x = -25[/tex]
We divide between 5 on both sides of the equation:
[tex]x = \frac {-25} {5}\\x = -5[/tex]
ANswer:
[tex]x = -5[/tex]
In the figure, Triangle BAT is congruent Triangle CAT. Which statement is true by CPCTC?
CPCTC = corresponding parts of congruent triangles are congruent
BA and CA are corresponding sides for both triangles, namely twins, BA ≅ CA.
Answer: [tex]\overline{BA}\cong\overline{CA}[/tex]
Step-by-step explanation:
Given : [tex]\triangle {BAT}\cong\triangle{CAT}[/tex]
The CPCTC property of congruent triangles says that the corresponding parts of congruent triangles are congruent.
Therefore, the the corresponding angles and sides of [tex]\triangle {BAT}\text{ and }\triangle{CAT}[/tex] are congruent.
i.e. [tex]\angle {BAT}\cong\angle{CAT}[/tex]
[tex]\angle {ATB\cong\angle{ATC}\\\\\[/tex]
[tex]\angle {TBA}\cong\angle{TCA}[/tex]
and
[tex]\overline{BA}\cong\overline{CA}\\\\\overline{AT}\cong\overline{AT}\\\\\overline{TB}\cong\overline{TC}[/tex]
So, from all the options [tex]\overline{BA}\cong\overline{CA}[/tex] is the true option.
What is the LCD of 5/6 and 2/5 ?
Answer:
30
Step-by-step explanation:
Find lowest common multiple of 5 and 6
Multiples of 5 Multiples of 6
5 × 1 = 5 6 × 1 = 6
5 × 2 = 10 6 × 2 = 12
5 × 3 = 15 6 × 3 = 18
5 × 4 = 20 6 × 4 = 24
5 × 5 = 25 6 × 5 = 30
5 × 6 = 30
5 × 7 = 35
5 × 2 = 10
5 × 3 = 15
5 × 4 = 20
5 × 5 = 25
5 × 6 = 30
5 × 7 = 35
30 is the lowest number which comes in both lists
It's 30... if your looking at a simple answer, it's 30.
tom opens a bank account and makes an initial investment of $500 the banker tells tom that he is going to recive and annula rate of 6% onhis investment find the bank balnace assuming that tom leaves the account untouhced for 15 years
Answer:
$950
Step-by-step explanation:
(500*6*15)/100 = 450 (applying the formula of simple interest)
450 + 500 ( adding the interest to the initial investment or princlple)
= 950 (bank balance after 15 years)
Hope this helps! :)
A student is attempting to solve a multi-step equation. Sample mathematical work is shown below. Which statement best applies to the sample mathematical work? Given the equation 35x – 10 = 5, I must solve for x. I first divide both sides by 35, which results in the equation x-10=1/7 I then add 10 to both sides, which gives me my final answer of x=71/70 A. The student incorrectly divided both sides by 35. B. The student incorrectly added 10 to both sides. C. The final answer is not reduced or simplified. D. The mathematical work shown is correct.
Answer:
A
Step-by-step explanation:
A: The student incorrectly divided both sides by 35. The student should first add 10 to both sides, obtaining 35x = 15, and then divide 15 by 35, obtaining the final answer 3/7.
Please Help me I really need it :)
Answer:
C
Step-by-step explanation:
For the given intervals
( - ∞, - 5) ← use any value < - 5 but not - 5, the parenthesis ) indicates that x is less than - 5 but not equal to - 5
(- 5, - 1) ← - 4, - 3, - 2 can be used but not - 5 or - 1
(- 1, 4) ← 0, 1, 2, 3 can be used but not - 1 or 4
(4, ∞ ) ← use any value > 4 but not 4
Hence
3 can be used in (- 1, 4)
- 6 can be used in (- ∞, - 5)
zero can be used in (- 1, 4)
- 5 cannot be used in any of the given intervals
Find the equation of the line.
Use exact numbers.
Y =
Suppose the leader of a camping trip is putting together a trail mix
raisins, and chocolate chips. The mix is to consist of equal parts raisins and chocolate. If
peanuts cost $2/lb, raisins cost $2.50/lb, and chocolate chips cost $4/lb, how much of each
should be mixed to create 20 lbs of trail mix that costs $2.75/lb?
Answer:
8 pounds of peanuts, 6 pounds of raisins and 6 pounds of chocolate chips
Step-by-step explanation:
Let x be the number of pounds of peanuts and y be the number of pounds of raisins and chocolate chips.
Peanuts cost $2 per pound, then x pounds cost $2x.
Raisins cost $2.50 per pound, then y pounds cost $2.50y.
Chocolate chips cost $4 per pound, then y pounds cost $4y.
In total, x+y+y=20 and those 20 pounds cost
2x+2.50y+4y=20·2.75.
Solve the system of two equations:
[tex]\left \{ {{x+2y=20} \\ \\ \\ \\ \\ \\ \atop {2x+6.5y=55}} \right.[/tex]
From the first equation:
[tex]x=20-2y[/tex]
Substitute x into the second equation:
[tex]2(20-2y)+6.5y=55\\ \\40-4y+6.5y=55\\ \\2.5y=15\\ \\25y=150\\ \\y=6\\ \\x=20-2\cdot 6=8[/tex]
A bicycle is marked 40% off the original price of $150. It is then taxed at 7 1/2%.
What is the final total cost of the bicycle
Answer:
$96.75
Step-by-step explanation:
A pharmacist found at the end of the day she had 5/4 as many prescriptions for antibiotics then tranquilizers. She had 18 prescriptions all together. How many did she have for tranquilizers?
Answer:
16. 5/3
Step-by-step explanation:
let the no of tranquilizer be x
therefore
5/4 + x =18
x= 18-5/4
= 16 5/3
What is the Prime factorization of 1323
Answer:3, 9, 27, 7, 189
Step-by-step explanation:
The prime factorization of 1323 involves breaking it down into prime factors that multiply together to give the original number, starting with the smallest prime.
Explanation:The prime factorization of 1323 is the process of breaking down the number into its prime factors, which are numbers that are prime and multiply together to give the original number, 1323. To find the prime factors, we start by dividing the number by the smallest prime number, which is 2. Since 1323 is odd, we move to the next prime number, which is 3. We find that 1323 is divisible by 3, so we can write 1323 as 3 × 441. We continue to take 441 and factor it further, eventually finding the complete prime factorization.
what is the vertex of the graph y=x^2+4x-1
a. (1,4)
b. (0,-1)
c. (-1,-4)
d. (-2,-5)
Answer:
Option d. (-2,-5)
Step-by-step explanation:
we know that
The equation of a vertical parabola in vertex form is equal to
[tex]y=a(x-h)^{2} +k[/tex]
where
a is a coefficient
(h,k) is the vertex of the parabola
In this problem we have
[tex]y=x^{2} +4x-1[/tex]
This is the equation of a vertical parabola open up
The vertex is minimum
Convert the equation in vertex form
Group terms that contain the same variable, and move the constant to the opposite side of the equation
[tex]y+1=x^{2} +4x[/tex]
Complete the square. Remember to balance the equation by adding the same constants to each side.
[tex]y+1+4=x^{2} +4x+4[/tex]
[tex]y+5=x^{2}+4x+4[/tex]
Rewrite as perfect squares
[tex]y+5=(x+2)^{2}[/tex]
[tex]y=(x+2)^{2}-5[/tex] -----> equation in vertex form
therefore
The vertex is (-2,-5)
Your parents gave you a gift card for your favorite coffee shop. The card was worth $50
when you got it. Each day, you buy a drink for $3. Which equation shows the value on
the gift card over time?
Final answer:
The equation that shows the value on the gift card over time is: Value on gift card = Initial value - Total amount spent.
Explanation:
The equation that shows the value on the gift card over time is: Value on gift card = Initial value - Total amount spent.
Since the initial value of the gift card is $50 and each day a drink costs $3, the equation can be written as: Value on gift card = 50 - 3x, where x represents the number of days.
This equation will give you the value remaining on the gift card after x days of buying a $3 drink.
I Need Help Answer Plz!!!
Answer:
10 inches
Step-by-step explanation:
All the sides are the same.